The Effect of Internet Banking Use and Customer Protection Against Cyber Crime at Bank Rakyat Indonesia - Muhammad Agreindra Helmiawan; Ade Iskandar Nasution (Journal of Islamic Economics and Business, 2022)
With the very rapid development of technology that helps humans in carrying out their activities, one of them in the banking world has emerged a product in the banking world, namely internet banking. The problem with technological developments is the higher the number of crimes that occur in the internet banking process. This study uses a quantitative research method with a case study of one of Indonesia's national banks, namely Bank BRI specific in BRI KC Majalaya. This study found that the use of internet banking has a significant effect on cybercrime at Bank BRI KC Majalaya and consumer protection has a significant effect on cybercrime.